5.1 Quaternary deposits of Bol'shoy Lyakhovsky Island. - Schirrmeister, Lutz; Schwamborn, Georg; Siegert, Christine; Babii, Olga (PANGAEA, 2017)
The heavy and light mineral composition of two fraction (63-125, 125-250 µm) from ca. 50 permafrost samples were studied in order to classify different stratigraphical stages.
Heavy and light minerals auf two differerent fraction from permafrost deposits of the Bol'shoy Lyakhovsky Island, expedition in 1999
Keywords: AWI_PerDyn; Permafrost Research (Periglacial Dynamics) @ AWI